2005
DOI: 10.1152/ajpregu.00290.2003
|View full text |Cite
|
Sign up to set email alerts
|

The influence of dehydroepiandrosterone and 8-OH-DPAT on the caloric intake and hypothalamic neurotransmitters of lean and obese Zucker rats

Abstract: The 5 HT(1A) receptor agonist 8-hydroxy-2-(di-n-propylamino)-tetraline (8-OH-DPAT) increases the food intake of satiated Zucker rats, both lean and obese. Associated with this increased intake are changes in the hypothalamic content of serotonin and its metabolite, 5-HIAA (5-hydroxyindole-3-acetic acid); serotonin is increased while the level of 5-HIAA is decreased. Analysis of individual 5-HIAA/5-hydroxytryptamine (5-HT) ratios, a measure of serotonin turnover indicate that 8-OH DPAT affected serotonin turnov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 25 publications
1
8
0
Order By: Relevance
“…influence on serotonin neurotransmission depends on the examined brain structure, but it does not seem to be dose-dependant, as similar results were obtained by groups using DHEA at doses 20 mg/kg (Porter et al, 2005) and 200 mg/kg (Nguyen et al, 1999).…”
Section: Discussionsupporting
confidence: 77%
“…influence on serotonin neurotransmission depends on the examined brain structure, but it does not seem to be dose-dependant, as similar results were obtained by groups using DHEA at doses 20 mg/kg (Porter et al, 2005) and 200 mg/kg (Nguyen et al, 1999).…”
Section: Discussionsupporting
confidence: 77%
“…Animal studies have consistently demonstrated reduced energy intake and weight loss due to exogenous DHEA‐S administration (42,44,45). In animals, these effects are dose‐dependent (41), differ between fatty phenotypes (42,43,47), and are attributed to appetite suppression from DHEA‐S acting via the central nervous system (48,49). In the present investigation, DHEA‐S was significantly higher during energy deprivation compared to energy balance.…”
Section: Discussionmentioning
confidence: 99%
“…We then assayed brain tissue to determine the role of hypothalamic and raphe monoamines. We hypothesize that DHEA will interfere with the orexigenic effects of NPY correspondingly to our recent study with 8-OH DPAT (Porter et al 2005) and that this effect will be mediated, at least in part, via hypothalamic monoamines.…”
Section: Introductionmentioning
confidence: 75%
“…Given the previous hypothesis, blocking the serotonin system locally in the VMH should inhibit the ability of DHEA to reverse the behavioural effects of NPY on food intake. This step is crucial given that in a similar study DHEA blocked the increase in food intake caused via 8-OH DPAT (Porter et al 2005); an agent proposed to lower serotonin release (Zifa and Fillion 1992) and activates the 5-HT 1A receptor (Gilbert et al 1988;Hutson et al 1998;Zifa and Fillion 1992). The contradiction arises in that while DPAT lowered serotonin turnover, DHEA failed to raise serotonin turnover levels back to control despite having a behavioural effect (Porter et al 2005).…”
Section: Discussionmentioning
confidence: 97%